ANALISIS TINGKAT KESEJAHTERAAN PEKERJA GIG DI INDONESIA - Sitorus, Aurelia Ananda; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research was conducted to determine the level of welfare of Indonesian gig workers in various fields. The method used is a quantitative method with primary data taken using a questionnaire from 250 respondents and then processed using multiple linear regression analysis methods. The research results show that job protection and income have a significant effect on the welfare of gig workers in Indonesia. Gig workers, most of whom do not work from the office, still need job protection and consider income an important factor that can influence their well-being. Meanwhile, social security is not a factor that can improve the welfare of gig workers in Indonesia because it is still hindered by several obstacles such as lack of socialization from the government and minimal literacy and concern for gig workers due to their busy lives and different work systems from wage earners.